ER-LD Membrane Contact Sites: A Budding Area in the Pathogen Survival Strategy - Rajendra Kumar Angara; Margaret F. Sladek; Stacey D. Gilk (Contact)
The endoplasmic reticulum (ER) and lipid droplets (LDs) are essential organelles involved in lipid synthesis, storage, and transport. Physical membrane contacts between the ER and LDs facilitate lipid and protein exchange and thus play a critical role in regulating cellular lipid homeostasis. Recent research has revealed that ER-LD membrane contact sites are targeted by pathogens seeking to exploit host lipid metabolic processes. Both viruses and bacteria manipulate ER-LD membrane contact sites to enhance their replication and survival within the host. This review discusses the research advancements elucidating the mechanisms by which pathogens manipulate the ER-LD contacts through protein molecular mimicry and host cell protein manipulation, thereby hijacking host lipid metabolic processes to facilitate pathogenesis. Understanding the crosstalk between ER and LDs during infection provides deeper insight into host lipid regulation and uncovers potential therapeutic targets for treating infectious diseases.